Metabolic alterations in the right anterior insula among patients with cirrhosis without overt hepatic encephalopathy: a magnetic resonance spectroscopy study - Huang, Nao-Xin; Huang, Hui-Wei; Dong, Qiu-Yi; Wen, Yu-Lin; Li, Dan; Li, Jian-Qi; Chen, Hua-Jun (Frontiers in Neurology, 2024)
Purpose We investigated metabolic alterations in the right anterior insula (rAI) in cirrhotic patients and determined its association with patients' cognitive dysfunction. Methods In this study, 31 healthy controls (HCs) and 32 cirrhotic patients without overt hepatic encephalopathy participated. Both blood ammonia level and Child-Pugh score were measured. The psychometric hepatic encephalopathy score (PHES) was used to evaluate cognitive function. 1H-magnetic resonance spectroscopy (MRS) data located in the rAI were recorded on a commercially available 3T magnetic resonance imaging scanner. The ratios of metabolites were measured, including N-acetylaspartate (NAA)/total creatine (tCr), glutamate plus glutamine (Glx)/tCr, myo-inositol (mI)/tCr, and total choline (tCho)/tCr. We adopted the non-parametric Mann–Whitney U-test for intergroup comparison of metabolic ratios. To determine the association between metabolite concentration and clinical parameters, we performed Spearman correlation analyses. Results Patients with cirrhosis performed worse on PHES in comparison with HCs (P < 0.001). Patients with cirrhosis had significantly decreased mI/tCr (0.87 ± 0.07 vs. 0.74 ± 0.19, P = 0.025) and increased Glx/tCr (1.79 ± 0.17 vs. 2.07 ± 0.29, P < 0.001) in the rAI. We did not observe any significant between-group differences in tCho/tCr and NAA/tCr. The blood ammonia level was correlated with Glx/tCr (r = 0.405, P = 0.022) and mI/tCr (r = −0.398, P = 0.024) of the rAI. In addition, PHES was negatively correlated with Glx/tCr of the rAI (r = −0.379, P = 0.033). Conclusion Metabolic disturbance of the rAI, which is associated with ammonia intoxication, might account for the neural substrate of cirrhosis-related cognitive dysfunction to some extent.